Thermal transformations of bismuth (III) tartrates - Liubov I. Afonina; Tatiana E. Timakova; Evgeniya V. Timakova; Konstantin B. Gerasimov; Yuri M. Yukhin (Chimica Techno Acta)
The processes of oxidative thermolysis of bismuth tartrates [Bi(NO3)(C4H4O6)]·3H2O and BiC4H3O6·H2O precipitated from bismuth nitrate solutions was studied by the methods of X-ray diffraction, thermal analysis, IR spectroscopy and chemical analysis. The staging of thermal transformation processes was determined. Morphological studies of initial precursors and the final products of their thermal transformations were carried out. The expediency of obtaining fine-crystal powders of the tetragonal bismuth oxide modification β-Bi2O3 with uniform sized particles by oxidative thermolysis of BiC4H3O6∙H2O was shown.